DAKWAH AKOMODATIF: SOLUSI DAKWAH APLIKATIF FUNGSIONAL PADA MASYARAKAT MULTIKULTURAL - Fahrurrozi Fahrurrozi (Universitas Islam Negeri (UIN) Mataram, 2017)
Da’wah in the reality of the society Indonesia multiple and plural gives a very wide space by The 1945 Constitution Article 29 paragraph 2 ensures the freedom of every citizen to embrace religion and trust and worship in accordance with his religion and his belief that. However, in practice, activities Da’wah in Indonesia still faces obstacles. Propagation is done by an individual or institutional basis, it still showed the selfishness and personal groups. With on behalf of truth and religion, their assault against another group or congregation. Problem calling other important enough is concerned the difference understand that often makes social relations with the dominant religion is compromised, even in certain levels could cause social insecurity. This article gives the concept of charity donations that is considered relevant to the context of the present model is the Da’wah accommodating, the focus was more on point accommodation to reality empirical sociological even theological society that multicultural. With this approach could be tested that Islam Rahman li al Alamein, and harmonization of the people in the midst of global challenges and technologies.